A Ritual Demystified: The Work of Anti-wonder among Sufi Reformists and Traditionalists in a Macedonian Roma Neighborhood - Oustinova-Stjepanovic, Galina (Religion and society, 2019)
This article describes how an iconic mystical Sufi ritual of body wounding, zarf, was stripped of its mystical credentials and conventional efficacy amid tensions between Rifai reformists and traditionalists in a small Roma neighborhood in Skopje, Macedonia. The death of a sorcerer and a funeral event-series set the scene for acts of anti-wonder' and demystification by the Rifai reformists. Despite the history of socialist secularism and inadvertently secularizing Islamic reforms in the region, demystification signaled not the loss of enchantment per se, but a competition for legitimate forms of wonder. In addition to accounting for socio-historical context and relational forms of Islam, the real challenge is how to see a demystified ritual for its explicit intellectual capacity to stimulate speculation about itself.